2014
DOI: 10.1021/es504016r
|View full text |Cite
|
Sign up to set email alerts
|

Methane Emissions from Process Equipment at Natural Gas Production Sites in the United States: Liquid Unloadings

Abstract: Methane emissions from liquid unloadings were measured at 107 wells in natural gas production regions throughout the United States. Liquid unloadings clear wells of accumulated liquids to increase production, employing a variety of liquid lifting mechanisms. In this work, wells with and without plunger lifts were sampled. Most wells without plunger lifts unload less than 10 times per year with emissions averaging 21,000-35,000 scf methane (0.4-0.7 Mg) per event (95% confidence limits of 10,000-50,000 scf/event… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
131
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(135 citation statements)
references
References 10 publications
4
131
0
Order By: Relevance
“…1) to 43 kg CO 2 eq/bbl, and the life cycle GHG emissions decrease from 89.1 to 89.0 g CO 2 eq/MJ gasoline. Although fugitive emissions do not impact the carbon intensity of Bakken crude fuels, we believe experimental investigations of tank vapor and other crude-specific emissions akin to the investigations of Allen et al for natural gas systems (37)(38)(39) are timely.…”
Section: Discussionmentioning
confidence: 92%
“…1) to 43 kg CO 2 eq/bbl, and the life cycle GHG emissions decrease from 89.1 to 89.0 g CO 2 eq/MJ gasoline. Although fugitive emissions do not impact the carbon intensity of Bakken crude fuels, we believe experimental investigations of tank vapor and other crude-specific emissions akin to the investigations of Allen et al for natural gas systems (37)(38)(39) are timely.…”
Section: Discussionmentioning
confidence: 92%
“…For example, the EPA reports that approximately 50,000 wells in the United States vent during liquid unloadings, resulting in 259 Gg/yr of methane emissions (EPA, 2015c). A small fraction of these venting wells, perhaps 3-5%, likely accounts for half of unloading emissions (Allen et al, 2015b). Similarly, multiple studies (Prasino 2013; Allen et al, 2015a;Gibbs, 2015) have found that a small subpopulation of pneumatic controllers (the largest source of greenhouse gases in the petroleum and natural gas supply chains) dominates emissions.…”
Section: Zavala Et Al 2015amentioning
confidence: 98%
“…Some short-duration events occur by design. For example, liquid unloadings can last for periods as short as a few minutes, yet during that period have emission rates equivalent to a thousand or more wells in routine operation (Allen et al, 2015b). Emissions can also be due to unplanned events.…”
Section: Spatial and Temporal Variability In Emissionsmentioning
confidence: 99%
“…• liquids unloading for all gas wells [29,44] However, there remains a lack of representative point-source data and an understanding of emissions variation across regions and over time, in particular with regards to extraction from coal bed methane, liquids unloading and pipework leaks from transmission, storage and distribution. Perhaps the largest gap in available data is for offshore extraction emissions: only one study on offshore gas extraction emissions has been found [30].…”
Section: Data Availabilitymentioning
confidence: 99%